STRATEGI PEMBELAJARAN DARING DAN LURING PADA MASA PANDEMI COVID-19 DI MI QUBA KOTA SORONG - Putri Putri; Suharmoko Suharmoko; Darnanengsih Darnanengsih (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2021)
This study aims to determine: 1) online and offline learning strategies used during the Covid-19 pandemic, and 2) obstacles in implementing online and offline learning strategies during the Covid-19 pandemic at MI Quba, Sorong City. This study uses a qualitative approach with a descriptive type of research. Data collection techniques were carried out by interviews and documentation. The research subjects were homeroom teachers for class IV-VI AB. The data analysis technique used is the Miles and Huberman model, namely data collection, data reduction, data presentation, and data conclusion/verification. Test the validity of the data using source triangulation and technical triangulation. The results showed that 1) the online learning strategies used were constructivist pedagogical strategies and offline learning strategies using cooperative learning strategies, 2) the obstacles faced in the application of online and offline learning strategies, the obstacles during online learning were in terms of facilities not all students have a cellphone, slow internet network, full cellphone memory, internet quota, and in terms of learning outcomes the homeroom teacher is not satisfied with learning because they cannot directly monitor students in the teaching and learning process so that students lack understanding of the subject matter presented. The obstacle faced by homeroom teachers during offline learning is the limited study time